2020
DOI: 10.2217/epi-2020-0048
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Resolution Peripheral Blood Methylome Profiling Reveals Signatures for Cholestatic Liver Disease

Abstract: Aim: To profile DNA methylation changes of primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC). Materials & methods: Patients with: PBC, PSC with inflammatory bowel disease (IBD), PSC without IBD, and age-, sex-matched controls were profiled for methylomes of peripheral blood by reduced representation bisulfite sequencing. Differentially methylated CpG (DMC) and differentially methylated region (DMR) were detected and compared. Results: We identified consistently altered DMCs and DMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The overall lack of large-scale differences in methylation between the various groups corroborates the observations made by Moore et al., where the authors did not observe large global methylation changes in the peripheral blood of patients with PSC compared to healthy controls and between patients with PSC with and without IBD ( 15 ). While peripheral blood is a practical tissue for biomarker use due to its ease of access, it contains a heterogeneous population of cells, which might be less representative for disease features, such as the PSC-UC-associated phenotypes that manifest primarily in the liver and gut tissue.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The overall lack of large-scale differences in methylation between the various groups corroborates the observations made by Moore et al., where the authors did not observe large global methylation changes in the peripheral blood of patients with PSC compared to healthy controls and between patients with PSC with and without IBD ( 15 ). While peripheral blood is a practical tissue for biomarker use due to its ease of access, it contains a heterogeneous population of cells, which might be less representative for disease features, such as the PSC-UC-associated phenotypes that manifest primarily in the liver and gut tissue.…”
Section: Discussionsupporting
confidence: 89%
“…While having a same-sex cohort decreases variance, it makes the observations less translatable to the general PSC-IBD population. While previous EWAS have indicated that DNA methylation profiles differ between males and females ( 72 ), limited to no sex-associated difference were reported in PSC-associated EWAS ( 15 , 16 ). One study did show an enrichment of differentially methylated CpG sites located on chromosome X in patients with PSC-IBD and PSC without IBD compared to controls but did not make a comparison with the methylomes of patients with PSC alone ( 15 ).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“… 8 In blood, differential methylation was largely split between hypomethylation and hypermethylation and enriched pathways included inositol phosphate metabolism (both diseases), IL-17 signaling (PBC), and TGF-β signaling (PSC). 9 While epigenome-wide approaches were used in these studies, sample sizes were small, and the use of reduced representation bisulfite sequencing limited downstream analytics. Here, we report an EWAS of a large cohort of patients with PSC and PBC and well-matched control groups using an array-based platform, the Illumina MethylationEPIC Bead Chip.…”
Section: Introductionmentioning
confidence: 99%